PROFESIONALISME PELAYANAN PUBLIK PADA PELAYANA E-KTP DI KECAMATAN PAKONG KABUPATEN PAMEKASAN - Muhammad Aly Umar (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2020)
The role of employee work professionalism is very much determined by the level of employee ability which is reflected in their daily behavior in the organization. The ability of employees to provide public services leads to the achievement of organizational goals that have been planned beforehand, for this reason the researcher conducted research on the professionalism of public services in Pakong Subdistrict, Pamekasan Regency, in this case the service for managing electronic identity cards (e-KTP). The purpose of this study was to determine the role of employee professionalism in public services, especially in the service of electronic identity cards (e-KTP) at the Pakong District Office, Pamekasan Regency, seen from the indicators of creativity, innovation, and responsibility. This research is intended to examine the implementation of the electronic identity card (e-KTP) program which is carried out at the Pakonng District Office, Pamekasan Regency. The formulation of the problem used is how professional are the District Office employees in the service of electronic identity cards (e-KTP) at the Pakong District Office? The method used is descriptive qualitative then the data collection techniques used are interviews, documentation, and observation. The data validation used was purposive sampling, namely sampling data sources with certain considerations and the data analysis technique was qualitative data analysis with analysis components, namely collected data, data classification, formation of conclusions and general characteristics. The results of this study indicate that the professionalism of employees in service electronic identity card (e-KTP) in Pakong District, Pamekasan Regency, is included in the good category. This is indicated by the following indicators: creativity is quite good, innovation is quite maximal and responsibility is good. Because every activity goes according to procedure.